Le sentiment d’efficacité personnelle des enseignants en gestion de classe et leur satisfaction au travail : le rôle explicatif des stratégies de gestion des comportements auprès des élèves qui présentent des problèmes de comportement extériorisés - Boudreault, Alexis; Lessard, Julie; Guay, Frédéric (Canadian Journal of Education/Revue canadienne de l’éducation, 2023)
This study tests a model in which teachers’ sense of self-efficacy in classroom management, punitive and positive verbal behaviour management strategies, and relationship to students’ externalizing behaviour problems each relate to teachers’ job satisfaction. The participants were 80 teachers from Quebec and Ontario. Each teacher provided assessments for two students in their class (n = 157) showing high levels of externalizing behaviour problems. The results of a structural equation model show that teachers’ sense of efficacy in classroom management is positively related to their job satisfaction and to the positive verbal strategies they use. On the other hand, the results also reveal that the overall level of externalizing behaviour problems of all students in the classroom is negatively associated with job satisfaction. The theoretical and practical implications of these findings are discussed, including the role that interventions might play in reducing students’ externalizing behaviour problems and promoting teachers’ job satisfaction.